Study on the homogeneity of tilted dendritic structures in single crystal superalloys - Xiaotan Yuan; Congjiang Zhang; Hongbin Yu; Weili Ren; Biao Ding; Haibiao Lu; Yunbo Zhong; Zuosheng Lei; Hui Wang; Qiuliang Wang; Peter K. Liaw; Xuezhi Qin; et al. (Journal of Materials Research and Technology, 2023)
Dendrites play a crucial role in the microstructure of single crystal superalloys, predominantly developing along the [001] orientation. The mechanical performance is greatly influenced by the uniform distribution of dendrites. During the solidification process, we frequently observe instances of dendrites deviating from the [001] orientation, resulting in tilted structures. These deviations give rise to both aligned and misaligned arrays within the transverse section. The study comprehensively examines the homogeneity of tilted dendritic structures. As solidification progresses, new dendrites within the aligned array tend to maintain a hexagonal structure. Simultaneously, the remaining metastable structures gradually transition into hexagonal structures. In contrast, various polygons mutually transform in misaligned array, resulting in a dynamic adjustment of their proportions. Consequently, the aligned array exhibits a higher proportion of hexagonal structures and a more uniform dendrite spacing compared to the misaligned array. Within the transitional region, an increase in heptagonal structures leads to heightened non-uniformity in dendrite spacing. The predominance of hexagonal structures can be attributed to their more uniform solute distribution, facilitated by the characteristics of the aligned array, which promote hexagonal structure formation by adjusting the solute field distribution. On the other hand, due to the random positioning of dendrites in the misaligned array, various stacking structures coexist in dynamic equilibrium. The research reveals an intrinsic relationship between macroscopic array patterns, stacking structures, dendrite spacing, and microscopic solute distribution. These findings provide a theoretical foundation for the production of high-quality single crystal dendritic structures and offer insights into their influence on material properties.